2010
DOI: 10.1002/adem.200900335
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Improving Tensile Ductility of Bulk Nanostructured Materials

Abstract: Strength and ductility are two of the most important mechanical properties of structural materials. High strength is desired for structural components so that they can carry high loads. Good ductility is essential to avoid catastrophic failure in load-bearing applications and is also very important for many shaping and forming operations. The ductility of materials is defined as the extent to which a material can be plastically deformed. Usually, ductility is measured as the elongation to failure in uniaxial t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 166 publications
(78 citation statements)
references
References 72 publications
1
75
0
2
Order By: Relevance
“…less heterogeneous regions, are thermally more stable. With respect to the high strength but low ductility of nanometals, the necessary structural adjusting to produces socalled bi-model or multi-modal grain size distribution has significantly optimized the strength and ductility combination [19,20]. The present investigation may provide with potential structural optimization strategy through adjusting the distribution and volume fraction of hard and soft regions by proper annealing treatment.…”
Section: Structural Designmentioning
confidence: 92%
“…less heterogeneous regions, are thermally more stable. With respect to the high strength but low ductility of nanometals, the necessary structural adjusting to produces socalled bi-model or multi-modal grain size distribution has significantly optimized the strength and ductility combination [19,20]. The present investigation may provide with potential structural optimization strategy through adjusting the distribution and volume fraction of hard and soft regions by proper annealing treatment.…”
Section: Structural Designmentioning
confidence: 92%
“…17 It follows that dislocation barriers are required within the grain interior where dislocations can be blocked and accumulate. Some successful strategies to this end include the use of growth twins, 18 deformation twinning, [19][20][21] stacking faults, 22,23 and second-phase particles/precipitates 24 as barriers. Since these approaches can also increase the strength, they often lead to a simultaneous increase in both strength and ductility.…”
Section: Authors' Notementioning
confidence: 99%
“…Therefore, annealing to lower the dislocation density without increasing the grain size is expected to improve the strain hardening and ductility. Indeed, it has been found that processing the UFG metals to a very large strain or annealing SPD-processed UFG metals for a very short time can enhance the ductility, 20,25,26 which could be due to both a lower dislocation density and a higher fraction of high-angle grain boundaries.…”
Section: Authors' Notementioning
confidence: 99%
“…In the past, quite frequently porosity from incomplete densification was still an issue with this technique. However, within the last decade, there are increasingly more examples and strategies for obtaining bulk, fully densified nanocrystalline materials produced via ball milling; 133 subsequent consolidation demonstrates that these materials can possess good ductilities while retaining much of the strength of nanocrystalline materials 119,122,134 (i.e., 14% tensile ductility or potentially higher in Refs. 119,122).…”
Section: Ductilitymentioning
confidence: 99%